Synthesis and Characterization of Amorphous TiO2 Anode Prepared by Anodizing Method for Na-ion Batteries - Dwi Indrawati; Nirwan Syarif; Dedi Rohendi (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2021)
Sodium ion battery (SIB) has engage sustainable alternative on replacing lithium ion batteries. The lower potential and larger ionic value has demanded on seeking a potential anode materials. Amorphous TiO2 prepared by electrochemical anodisation technique has provide a suitablility as anode SIB materials, which approved by conducting XRD, FTIR, and SEM-EDX measurements. Electrochemical performance was tested with variations in the concentration of NaOCl4 electrolyte in propylene carbonate (PC) solvent. Diffractogram of TiO2 showed the only peaks of Ti was observed at 2θ = 40.34. The TiO2 IR spectrogram shows that the absorption band at 507 cm-1 is the peak of the vibration characteristics of the Ti-O bond and the peak of 975 cm-1 corresponds to Ti-O-Ti bond. SEM-EDX image analysis showed the morphology of TiO2 was smooth without pore with a ratio of Ti: O elemental composition of 1: 2. Voltammogram showed the anodes in 0.5 M NaOCl4 electrolyte in PC solvent has a good stability potential windows with the high current density 1.2 mA and the capacity of 0.037 F/g